2013
DOI: 10.1074/jbc.m113.485987
|View full text |Cite
|
Sign up to set email alerts
|

Retinoic Acid-related Orphan Receptor α Regulates Diurnal Rhythm and Fasting Induction of Sterol 12α-Hydroxylase in Bile Acid Synthesis

Abstract: Background: Sterol 12␣-hydroxylase catalyzes cholic acid synthesis. ROR␣ is a cholesterol-activated and fasting-induced nuclear receptor and core clock gene. Results: Upon fasting, glucagon/PKA phosphorylated and stabilized ROR␣ protein to induce CYP8B1 and diurnal rhythm. Conclusion: ROR␣ is a key regulator of CYP8B1 that regulates bile acid and cholesterol homeostasis. Significance: Antagonizing ROR␣ activity may be a therapeutic strategy for treating non-alcoholic fatty liver disease and diabetes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
40
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
2
1

Relationship

3
7

Authors

Journals

citations
Cited by 64 publications
(42 citation statements)
references
References 44 publications
1
40
1
Order By: Relevance
“…A comparable 4-times-a-day feeding experiment with a high cholesterol diet in rats reported results in line with ours, showing that hepatic Cyp7a1 expression remained rhythmic with regular feeding, although the timing of the peak shifted (Yamajuku et al 2009). Indeed, the core clock machinery can directly influence transcription of these genes, for example, RORα can influence the diurnal rhythm of Cyp8b1 expression (Pathak et al 2013) and DBP and REV-ERB stimulate the transcription of Cyp7a1 (Duez et al 2008;Lavery and Schibler 1993). In addition, CLOCK can directly stimulate Shp expression (Bavner et al 2005;Kerr et al 2002), by binding its E box (Oiwa et al 2007;Pan et al 2010).…”
Section: Discussionmentioning
confidence: 99%
“…A comparable 4-times-a-day feeding experiment with a high cholesterol diet in rats reported results in line with ours, showing that hepatic Cyp7a1 expression remained rhythmic with regular feeding, although the timing of the peak shifted (Yamajuku et al 2009). Indeed, the core clock machinery can directly influence transcription of these genes, for example, RORα can influence the diurnal rhythm of Cyp8b1 expression (Pathak et al 2013) and DBP and REV-ERB stimulate the transcription of Cyp7a1 (Duez et al 2008;Lavery and Schibler 1993). In addition, CLOCK can directly stimulate Shp expression (Bavner et al 2005;Kerr et al 2002), by binding its E box (Oiwa et al 2007;Pan et al 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Other nuclear receptors, such as the pregnane X receptor (PXR)[20] and vitamin D receptor (VDR) [21], can also regulate BA synthesis by suppressing CYP7A1. Moreover, activation of the nuclear receptor RORα can modulate 12α-hydroxylase (CYP8B1) expression [22, 23]. …”
Section: Bile Acid Synthesis and Regulationmentioning
confidence: 99%
“…36 ROR a has previously been described to induce the expression of CYP8B1 during fasting; in a study by Pathak et al a functional ROR a response element was found in the CYP8B1 promotor. 38 With this knowledge, we decided to investigate ROR a expression following dexamethasone treatment and indeed the expression of ROR a was increased. Blocking GR signaling with RU486 resulted in a reduced but not blocked expression of ROR a.…”
Section: Journal Of Clinical and Experimental Hepatologymentioning
confidence: 99%